Normative analysis of the crime of misuse of privileged information (insider trading) in Brazil (Research, Society and Development, 2022)
Due to the increase in the practice of the crime of improper use of privileged information, known as insider trading, it was decided to carry out a historical survey related to the ways of combating crime in North America, as well as a study of the historical and legislative evolution in the Brazil in order to present how the problem is being conducted in the country. A bibliographic, doctrinal and jurisprudential review and presentation of results in a descriptive way were used as a method for data collection. It was concluded that in Brazil the misuse of privileged information is punished at the administrative level, by means of a warning, fine and suspension of the exercise of an administrative position; in the civil sphere, through indemnity sanctions and, in the criminal sphere, with imprisonment from 1 to 5 years and a fine of up to 3 times the amount obtained as an advantage. Law no. 10,303/2001 simplified the criminal type, aiming to incriminate all offenders. However, because it is a complex crime and difficult to prove, it is observed in practice a reduced number of convictions. Constant technological advances provide new modalities of operations in the securities market, making the activities of supervision, inspection and application of penalties increasingly challenging.